Lie symmetry analysis of a pseudoparabolic PDE: Power law in diffusion coefficient with constant viscosity - Maile Khati; Motlatsi Molati (Partial Differential Equations in Applied Mathematics, 2021)
We perform symmetry analysis of a partial differential equation (PDE) of pseudoparabolic form which models solvent uptake in polymeric solids; a special case of power law for diffusion coefficient and constant viscosity is considered. Optimal systems of one-dimensional subalgebras for various model parameters are employed for symmetry reductions and construction of invariant solutions.